Paternalistic Leadership in Korean Small and Medium Scale Enterprises: Applicability of a Turkish Paternalism Scale - Ulaş Çakar; Haeeun Kim (Journal of Human and Work)
Social and cultural exchange between Korea and Turkey has been rapidly increasing and is expected to be accelerated for the future. Especially business exchange is interest of many people in both countries. This paper aims to provide insights for business people in Korea and Turkey to understand each country’s cultural aspects. Among different perspectives, paternalism is focused in the study. Paternalism is an important intersection of both cultures but it did not receive much attention. Even though both Turkish and Korean leaders are paternalistic, the origin of the characteristic is based on different background. The current studies of paternalism in Korea are based on Confucianism and economic crisis whereas those of Turkey are based on nomadic history, military Coup d'Etat, complicated bureaucracy, and economic instability. Using a paternalism scale developed with Turkish sample, this study measured Korean employees’ perception on paternalism and paternalistic leadership. The results showed that the scale is applicable in Korean organizations as well.